Enhanced kiosks mapping on traditional market using Apriori Algorithm / Ardiansyah Dores, and Tazkiyah Herdi - Dores, Ardiansyah; Hasani, Rifqi; Herdi, Tazkiyah (Faculty of Computer and Mathematical Sciences, 2021)
Traditional market requires realignment of the existing problems so that the market is more comfortable to visit. In this study the author experimenting with buyer transactional data using market analysis method to see association rules between numbers of attributes of a kiosk. The algorithm used here is a priori algorithm, the data used are questionnaire data from 250 respondents, from the data taken 120 data used as training data, for the process of making data models. In this market there are 288 kiosks that grouped into 14 categories. The results in the F1 process with the 30 thresholds, obtained 6 categories, up to the F3 process with the determination of the 20 thresholds, obtained 3 categories. Based on the results of research in accelerate the process of forming item-set combinations of transactions. Also, this research can help in giving recommendations and considerations to traditional market developers in determining kiosk layout.